Computational Characterization of Single-Electron Transfer Steps in Water Oxidation - Adiran de Aguirre; Ignacio Funes-Ardoiz; Feliu Maseras (Inorganics, 2019)
The presence of single-electron transfer (SET) steps in water oxidation processes catalyzed by first-row transition metal complexes has been recently recognized, but the computational characterization of this type of process is not trivial. We report a systematic theoretical study based on density functional theory (DFT) calculations on the reactivity of a specific copper complex active in water oxidation that reacts through two consecutive single-electron transfers. Both inner-sphere (through transition state location) and outer-sphere (through Marcus theory) mechanisms are analyzed. The first electron transfer is found to operate through outer-sphere, and the second one through inner-sphere. The current work proposes a scheme for the systematic study of single-electron transfer in water oxidation catalysis and beyond.